ANALYZING THE FINANCIAL STATEMENT USING HORIZONTAL – VERTICAL ANALYSIS TO EVALUATING THE COMPANY FINANCIAL PERFORMANCE PERIOD 2012-2016 (CASE STUDY AT PT. UNILEVER INDONESIATBK) - Lakada, Maharani Nadia; Lapian, S.L.H.V. Joice; Tumiwa, Johan R. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The globalization of markets makes every business activity transcends the national border One of the multinational corporations that operated in Indonesia is PT. Unilever Indonesia Tbk. to survive and compete in the market the company not only focused on the strategy but also expected to be able to pay attention to the importance of financial statement for the continuity of the company in the market. This study is aim to know the financial performance of PT. Unilever Indonesia Tbk from 2012 to 2016.The researcher analyzed the data based on the secondary data which are the financial statements of PT. Unilever Indonesia Tbk from 2012-2016 by using Horizontal and Vertical analysis these two methods is used which aims to analyze the company financial performance. The secondary data is gathered through official site of Indonesia Stock Exchange that has the financial statement of PT. Unilever Indonesia Tbk. Descriptive quantitative approach is used in this research. After applied the horizontal and vertical analysis as a tools to evaluating the company financial performance, the result shows that the financial performance of PT. Unilever Indonesia Tbk has a good performance every analyzing year. Keywords: horizontal Analysis, vertical Analysis, financial performance